Computer-aided design of feedback control systems for time response - Maday, Clarence J. 1929- (Kogan page, 1987)
The book will be of interest to control and instrumentation engineers who are familar with the analytical techniques of control theory and analysis, and to the engineer who is skilled in plant operation but unfamiliar with the automatic control of the plant. The book also aims to narrow or bridge the gap between the analyst and the operating engineer. This book should be of interest to control and instrumentation engineers.